In situ conservation breeding and the role of zoological institutions and private breeders in the recovery of highly endangered Indonesian passerine birds. Issue 1 (9th January 2014) - Owen, A.; Wilkinson, R.; Sözer, R.
<x xml:space="preserve">Abstract</x> Indonesian birds are especially threatened both by habitat loss and trapping for the cage‐bird trade. This paper describes recent zoo‐supported work at Cikananga Wildlife Center, Java, for the conservation breeding of a number of threatened passerine birds. The founder populations of these birds were obtained from local private bird keepers. Zoos and similar‐minded conservation organizations have backed this work through both funding and technical support. Conservation breeding has been highly successful for the Black‐winged starling Sturnus melanopterus and Sumatran laughingthrush Garrulax bicolor. A more recently initiated programme for Javan green magpie Cissa thalassina has already resulted in breeding success and another programme has recently been initiated for the Rufous‐fronted laughingthrush Garrulax rufifrons. Reintroduction trials have already been initiated for Black‐winged starling and others are at the planning stages.